Synchronization of Laws and Regulations Promulgated in the Indonesian Law Country according to the Principles of Establishing Legislation - Muhapilah, Siti Opih; Sibuea, Hotma P.; Tumanggor, M. S.; Widijowati, Rr. Dijan (Green Publisher, 2023)
The stages of forming laws and regulations are mentioned in Article 1 paragraph (1) of Law Number 12 of 2011 which starts from planning, preparation, preparation techniques, formulation, discussion, approval, promulgation, and dissemination. Among the series of processes above, there is a process that is not explicitly stated but has a very important role, namely the process of harmonization. The research method used in this study is a normative juridical research method through literature study which examines primary, secondary and tertiary legal materials. The formulation of Article 1 point 1 of Law Number 12 of 2011 needs to be amended and added a new article formulation regarding the harmonization process at the stage of forming statutory regulations promulgated in state news. Second, the formulation of the new article which regulates the mechanism and procedures for the process of harmonization in the formation of statutory regulations promulgated in the state gazette reads as follows